Investigating Speaking Anxiety In Virtual World - Ulfa Nur Agussetia; Melisa Sri; Samuel Agus Triyanto (Jurnal Siliwangi: Seri Pendidikan, 2021)
The purpose of this study is to investigate speaking anxiety that occurred in the virtual world experienced by the higher education students in a speaking class since they were assigned to upload their self-recorded video to a social media that is currently used as a learning platform in a public speaking course, Facebook. As an alternative strategy to build speaking confidence because the students had sufficient time to prepare and upload the best video on the platform, still their speaking anxiety can be seen well. Accordingly, the researchers are interested in investigating the factors associating the speaking anxiety. Semi structured interviews were conducted to two undergraduate EFL students who had taken the Public Speaking subject.  The obtained data were analyzed using Miles and Huberman framework (1994). The findings reveal that factors causing speaking anxiety in the virtual world are cognitive, linguistic and affective, learning experiences, activities and habits out-of- class, and environments.